THE ROLE OF NON-GOVERNMENTAL ORGANIZATION IN CREATING AWARENESS OF GLOBAL ENVIRONMENTAL ISSUES: DISCOURSE ANALYSIS OF THE 2016/2017 GREEN SCHOOL ANNUAL REPORT - Dwi Nanda Listya Utama (JARES (Journal of Academic Research and Sciences), 2020)
As a Non-Governmental Organization, Green School Bali takes its role not only to educate young generation, but also to creat awareness about environmental issue. This study used qualitative research and theory of discourse analysis. All data collected both from Green School Bali annual report and also print and online sources. The researcher found out that Green School Bali has played a role in the implementation of mobilization by providing schools and all the attributes in it that were very concerned and also supported the elements of sustainability for a better long-term life. Secondly, Green School Bali also has acted as a service delivery actor by directly involving in maintenance efforts as well as counseling about the importance of maintaining the environment. Thirdly, as a catalyst, Green School Bali has succeeded in inspiring many groups to care about environment. And as a partner, Green School Bali has established cooperation with several parties to support sustainable lifestyles and also raise the global public awareness of the sustainability system.